Posterior reversible encephalopathy syndrome with essential thrombocythemia: A case report. Issue 34 (August 2019) - Zhang, Yunqiao; Lu, Zixiang; Li, Yanping; Wu, Jie; Liu, Ting; Xie, Xian; He, Xiaolin; Zeng, Yong
Abstract: Rationale: Posterior reversible encephalopathy syndrome (PRES) is a rare neurological disease of the posterior subcortical white matter that manifests as headache, seizures, visual impairment, disturbance of consciousness, and changes in mental state. While PRES is associated with specific imaging findings involving the posterior circulation area of the brain. In the present study, we report the first case of PRES associated with essential thrombocythemia (ET). Patient concerns: A 49-year-old man suddenly experienced headache, followed by the gradual appearance of consciousness disorders and mental behavior abnormalities. Neurological tests showed that the patient had a Glasgow Coma Scale score of 12, normal muscle strength and tension of the limbs, and was negative for meningeal irritation. Diagnosis: Magnetic resonance imaging of the brain showed extensive vasogenic edema in the deep white matter of the right cerebellum and the left occipital and temporal lobes and a diagnosis of PRES was considered. Routine blood test showed that his platelet count was markedly increased, and the JAK2 V617F mutation analysis with allele-specific real-time polymerase chain reaction was positive. The bone marrow biopsy indicated an increasing number of megakaryocytes. These findings indicated ET. Interventions: PRES was treated with a dehydrating agent and supportive and symptomatic treatments. Aspirin tablets were prescribed to address the patient's ET. Outcome: After treatment, the abnormal findings on head imaging were completely reversed. His neurological symptoms were completely relieved. Lessons: PRES may be correlated with ET; specifically, ET may trigger PRES and be a risk factor for the acute onset of neurological deficits.